Feasibility of Multiple Repeat Gamma Knife Radiosurgeries for Trigeminal Neuralgia: A Case Report and Review of the Literature. (14th July 2011) - Jones, Guy C.; Elaimy, Ameer L.; Demakas, John J.; Jiang, Hansi; Lamoreaux, Wayne T.; Fairbanks, Robert K.; Mackay, Alexander R.; Cooke, Barton S.; Lee, Christopher M.
Abstract : Treatment options for trigeminal neuralgia (TN) must be customized for the individual patient, and physicians must be aware of the medical, surgical, and radiation treatment modalities to prescribe optimal treatment courses for specific patients. The following case illustrates the potential for gamma knife radiosurgery (GKRS) to be repeated multiple times for the purpose of achieving facial pain control in cases of TN that have been refractory to other medical and surgical options, as well as prior GKRS. The patient described failed to achieve pain control with initial GKRS, as well as medical and surgical treatments, but experienced significant pain relief for a period of time with a second GKRS procedure and later underwent a third procedure. Only a small subset of patients have reportedly undergone more than two GKRS for TN; thus, further research and long-term clinical followup will be valuable in determining its usefulness in specific clinical situations.